Reflexiones sobre la movilidad de la población indígena en México : desde la integración hasta la globalización - Martha Judith Sánchez Gómez (Les Cahiers ALHIM)
The aim of the article is to provide an overview of the history of indigenous migration in Mexico from the early decades of the twentieth century to the present. This is analyzed in the light of national socioeconomic changes that have influenced the types and characteristics of migration. Although the explanation of migration is more complex, it is important to bear in mind that these changes form the broader context in which it takes place, and to which indigenous people have responded, creating and recreating different strategies and types of mobility.